Bone marrow mesenchymal stem cells inhibit cardiac hypertrophy by enhancing FoxO1 transcription. (22nd October 2020) - Qiu, Jiantao; Xiao, Huaiteng; Zhou, Shunchang; Du, Weimin; Mu, Xiang; Shi, Guangjun; Tan, Xueying
Abstract: Bone marrow–derived mesenchymal stem cells (BMSCs) have therapeutic potential for certain heart diseases. Previous studies have shown that stem cells inhibit cardiac hypertrophy; however, it is necessary to explore the mechanisms underlying this effect. This study aimed to investigate the possible mechanism underlying the inhibitory effect of BMSCs on cardiomyocyte hypertrophy. We induced cardiomyocyte hypertrophy in cultured rat cells through isoproterenol (ISO) treatment with or without BMSC coculture. A microarray was performed to analyze messenger RNA expression in response to ISO treatment and BMSC coculture. Pathway enrichment analysis showed that the expression of differential genes was closely related to the 5′‐adenosine monophosphate‐activated protein kinase (AMPK) signaling pathway and that the expression of forkhead box O 1 (FoxO1) was significantly increased in the presence of BMSCs. Furthermore, we determined the expression levels of p‐AMPK/AMPK and p‐FoxO1/FoxO1 by western blot analysis. The expression of p‐AMPK/AMPK was upregulated, whereas that of p‐FoxO1/FoxO1 was downregulated upon coculturing with BMSCs. The AMPK‐specific antagonist Compound C inhibited the downregulation of p‐FoxO1/FoxO1 induced by the BMSC coculture. Furthermore, treatment with the specific FoxO1 antagonist AS1842856 reduced the inhibitory effects of BMSCs on cardiomyocyte hypertrophy in vivo and in vitro. Our present study demonstrates the inhibition of cardiomyocyte hypertrophy by BMSCs, which occurs partly through the AMPK–FoxO1 signaling pathway.